Validity of a Tympanic Thermometer and Thermal Imaging Camera for Measuring Core and Skin Temperature during Exercise in the Heat. Issue 1 (2nd January 2020) - Fenemor, Stephen P.; Gill, Nicholas D.; Sims, Stacy T.; Beaven, C. Martyn; Driller, Matthew W.
ABSTRACT: This study compared criterion to minimally invasive, practical measures of core (Tc ) and skin (Tsk ) temperature during 30 min of moderate-intensity cycle exercise in a heat chamber (35°C, 60% rH). Tc was monitored using a core temperature pill (Tc(Pill) ) and tympanic thermometer (Tc(Tymp) ) during rest, exercise, and recovery in 15 participants. Tsk was monitored using hard-wired skin thermistors attached to a data logger (Tsk(T) ) and a thermal imaging camera (Tsk(IR) ) in 11 participants. Tc measurement resulted in no significant difference ( p > 0.05), a mean bias of 0.1°C, coefficient of variation (CV%) of 1.0%, and correlation of r = 0.74 between devices. Tsk measurement resulted in a significant difference ( p = 0.01), a mean bias of 0.6°C, CV% of 2.3%, and correlation of r = 0.61 between devices. Tc(Tymp) demonstrated acceptable agreement with Tc(Pill) ; however, caution is advised when using Tsk(IR) to give accurate measures of Tsk during exercise.